Florida Cracker Cattle - Jorge R. Rey (EDIS)
AN240, a 4-page illustrated fact sheet by Jorge R. Rey, describes this small to moderately-sized breed of cattle descended from the original cattle brought to Florida by the Spanish in the 1500s — history, breed characteristics, beef, organizations, and contacts. Published by the UF Department of Animal Sciences, May 2010.